PhnW-PhnX Pathway in Dinoflagellates Not Functional to Utilize Extracellular Phosphonates - Cui, Yudong; Lin, Xin; Zhang, Huan; Lin, Lingxiao; Lin, Senjie (Frontiers in Marine Science, 2016)
Phosphorus (P) is an essential nutrient for marine phytoplankton but its preferred form, dissolved inorganic phosphorus (DIP), is often limited in the euphotic zone of the ocean. Many phytoplankton species have developed the ability to utilize dissolved organic phosphorus (DOP) such as phosphoesters or phosphonates. Phosphonates are characterized by the stable C-P bond and its utilization is known to rely on either a C-P lyase pathway or C–P hydrolase pathways in bacteria. In this study by transcriptomic analysis we detected the genes encoding the C-P hydrolase pathway enzymes PhnW and PhnX in Karlodinium veneficum and other dinoflagellates. However, we found that these dinoflagellates are unable to utilize the presumably dominant type of phosphonate in the ocean, 2-aminoethylphosphonic acid (2-AEP), under the antibiotic-treated condition. In accordance, our RT-qPCR and proteomic analyses of K. veneficum grown on 2-AEP showed no up-regulation of PhnW and PhnX at both transcriptional and translational levels. Nevertheless, the genes related to phosphonate biosynthesis and utilization were widely found in dinoflagellates. Taken together our results suggest that the PhnW-PhnX pathway in dinoflagellates may serve for intracellular phosphonate metabolism instead of scavenging environmental phosphonates.